2021
DOI: 10.1111/ijlh.13513
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evidence of LEF1 isoforms in childhood acute lymphoblastic leukemia

Abstract: Introduction The lymphoid enhancer factor 1 (LEF1) is a DNA‐binding transcription factor that functions in the Wnt signaling pathway. Increased LEF1 activity is associated with progression of several types of cancer including leukemia. Here, we investigated LEF1 isoform expression and genomic variations in acute lymphoblastic leukemia (ALL). Methods LEF1 isoform expression was evaluated by quantitative real‐time PCR in 87 newly diagnosed childhood ALL patients and controls. Moreover, Western blot analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…In our previous study, we showed that pediatric ALL patients have increased FL-LEF1 expression and an abnormal ratio of long and short LEF1 isoforms have been found in B and T cell ALL (13). Here we defined the different expression patterns of LEF1 isoforms among adult lymphoid and myeloid malignancies and showed that although lymphoid and myeloid malignancies had significantly increased LEF1 expression, lymphoid group patients have significantly aberrant LEF1 activity according to the myeloid patients' group.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In our previous study, we showed that pediatric ALL patients have increased FL-LEF1 expression and an abnormal ratio of long and short LEF1 isoforms have been found in B and T cell ALL (13). Here we defined the different expression patterns of LEF1 isoforms among adult lymphoid and myeloid malignancies and showed that although lymphoid and myeloid malignancies had significantly increased LEF1 expression, lymphoid group patients have significantly aberrant LEF1 activity according to the myeloid patients' group.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous study showed that pediatric T-cell and B-cell ALL patients have differential expression of LEF1 variants (13). Therefore, in this study, we focused on LEF1 isoforms' expression in a group of adult lymphoid and myeloid hematological malignancies and found tissue-specific differential expression for LEF1 gene variants.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other murine models of T-ALL, including those arising in Tcf7 -/and Ikzf1 -/mice also show increased expression of Lef1 (32,33). Recently, a study of childhood ALL, including 28 patients with T-ALL, revealed a positive prognostic value to high LEF1 expression and a second study confirmed this for specific LEF1 isoforms (34,35). However, in a study of adult T-ALL, 25% of patients had elevated expression of LEF1 that was associated with a poor prognosis (36).…”
Section: Introductionmentioning
confidence: 95%
“…Among the identified cancers, over ten high-incidence malignancies result from abnormal activation of the Wnt signaling pathway, including colorectal cancer, 7 lung cancer, 8 breast cancer, 9 and childhood acute lymphoblastic leukemia. 10 Several studies have confirmed that Wnt signaling pathway imbalance can facilitate oral cancer development, 11 and its abnormal activation can directly influence the prognosis of patients with oral cancer. 2 …”
Section: Introductionmentioning
confidence: 99%